Women In Asia And Africa: An Interdisciplinary History-Based Readings Course - Dunn, Joe (Teaching History: A Journal of Methods, 2007)
My teaching is grounded in an international perspective and in student-centered active pedagogy. The goal is for students to assume responsibility for their own learning, and I use student peer modeling as a means to achieve that objective. I am convinced that the best learning environment provides students the opportunity to read extensively, to write about what they read, and to talk about their reading and written commentary. Most of my courses employ this pedagogy.1 I have selected one course to describe how the process works. "Women in Asian and African Cultures" might be my favorite offering of all the myriad of courses that I teach, and it is one of the most highly rated among my students.